Microcredit for people affected by HIV and AIDS: Insights from Kenya - Dipankar Datta; James Njuguna (Taylor & Francis Group, 2008)
Consequences of HIV and AIDS are exponential in Kenya, touching not only the health of those infected, but also depleting socioeconomic resources of entire families. Access to financial services is one of the important ways to protect and build economic resources. Unfortunately, the norm of financial viability discourages microfinance institutions from targeting people severely impacted by HIV and AIDS. Thus, HIV and AIDS service NGOs have been increasingly getting involved in microcredit activity in recent years for economic empowerment of their clients. Despite limited human resources and funding in the area of microcredit activity, these NGOs have demonstrated that nearly 50% of their microcredit beneficiaries invested money in income-generating activities, resulting in enhancement to their livelihood security. In the short term these NGOs need to improve their current practices. However, this does not mean launching microfinance initiatives within their AIDS-focused programmes, as financial services are best provided by specialised institutions. Longer-term cooperation between microfinance institutions and other AIDS service organisations and donors is necessary to muster appropriate and rapid responses in areas experiencing severe impacts of HIV and AIDS.